Assessment of criteria influencing the location of healthcare facilities in small and hard-to-reach areas - I. A. Deev; A. V. Polikarpov; N. A. Golubev; S. V. Moravskaya; O. S. Kobyakova (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To identify and systematize the criteria influencing the location of healthcare facilities in small and hard-to-reach areas.Material and methods. Within the study, regulatory legal acts of the Russian Federation and methodological guidelines on territorial planning were analyzed. Content analysis and statistical methods were used.Results. The following criteria for a comprehensive assessment of the location of healthcare facilities should be used: 1. Age structure of the population. 2. Distance to a similar medical organization. 3. Population size within the working radius of the organization. 4. Availability of public roads (criteria and categories of roads). 5. Availability of public transport. 6. Climatic. 7. Availability of medical workers residing in the locality. 8. Availability of mobile medical teams. 9. Dilapidation and breakdown of buildings. Taking into account various criteria affecting the accessibility of primary health care to a patient, it is possible to develop and implement management decisions on the rational placement of healthcare facilities at the regional level with detail for each locality.Conclusion. The use of criteria in territorial planning for a comprehensive assessment of the location of healthcare facilities makes it possible to take into account regional climatic, geographic, infrastructural, social and other features of the Russian constituent entities. This contributes to the implementation of development targets for primary health care in small and hard-to-reach areas.